The genus Idmon de Nicéville (Lepidoptera: Hesperiidae) from China, with description of two new species - Fan, Xiaoling; Wang, Min; Zeng, Ling (Zootaxa, 2007)
The skipper genus Idmon de Nicéville is surveyed fom China, two new species, I. flavata sp. nov. from Yinggeling in Hainan and I. bicolora sp. nov. from Mt. Nanling in Guangdong, are described and illustrated. Yanoancistroides Huang, 1999 is proved to be a new synonym of Idmon. Two new combinations, I. sinica (Huang, 1997) and I. fujianana (Chou & Huang, 1994) are proposed. A key to Chinese species is given.